2015
DOI: 10.1107/s2053273315005574
|View full text |Cite
|
Sign up to set email alerts
|

Iterative projection algorithms in protein crystallography. II. Application

Abstract: Iterative projection algorithms (IPAs) are a promising tool for protein crystallographic phase determination. Although related to traditional density-modification algorithms, IPAs have better convergence properties, and, as a result, can effectively overcome the phase problem given modest levels of structural redundancy. This is illustrated by applying IPAs to determine the electron densities of two protein crystals with fourfold non-crystallographic symmetry, starting with only the experimental diffraction am… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
24
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 13 publications
(24 citation statements)
references
References 49 publications
0
24
0
Order By: Relevance
“…(4) at iteration n, and its Fourier transform, are used. We use the R-factor (R), mean phase error (Φ), and map correlation coefficient (C) [12] to monitor convergence [17,10].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…(4) at iteration n, and its Fourier transform, are used. We use the R-factor (R), mean phase error (Φ), and map correlation coefficient (C) [12] to monitor convergence [17,10].…”
Section: Resultsmentioning
confidence: 99%
“…Liu et al (2012) [8] and He and Su (2015) [7] have applied the HIO algorithm with a solvent flatness constraint to a number 155 of solved proteins with high (> 65%) solvent content. Recently, Lo et al (2015) [10] applied the difference map algorithm to two solved protein structures with lower (∼50%) solvent content by incorporating a NCS constraint. Here we describe in detail application of the difference map algorithm to ab initio phasing of a previously solved icosahedral virus using the experimental diffraction data, 160 and starting with only a spherical shell envelope.…”
Section: Iterative Projection Algorithmsmentioning
confidence: 99%
See 1 more Smart Citation
“…Despite the existence of good physical methods for phasing the X-ray reflections of a protein crystal, direct phasing remains a challenging theoretical problem. Iterative projection algorithms have been widely used for phase retrieval [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17].…”
Section: Introductionmentioning
confidence: 99%
“…For crystals with high solvent content or with adequate non-crystallographic symmetry (NCS), it has been demonstrated that direct phasing is possible [10,12,13]. Completely ab initio phasing using an iterative algorithm has been reported [13].…”
Section: Introductionmentioning
confidence: 99%